The digital ethics - Zulhuda, Sonny (2020)
In this presentation as a lecture to IT students, the presenter discusses the nature, scope and application of the digital ethics at the current digital environment. Key points include the definition of digital ethics, the need to build a data culture, what Islam says about data culture and digital ethics, and the emerging issues surrounding the digital ethics.